Desenvolvimento corporal de bovinos terminados em confinamento, submetidos a diferentes taxas de ganho de peso na recria - Severo, Marcelo Machado (2019)
The objective of the present study was to verify the animal performance and carcass characteristics of beef cattle when reared under different live weight gains. The animals remained for 91 days in the rearing phase, where they were divided into 3 experimental groups: A) animals without food restriction (High GMD=0.846kg); B) Animals with moderate food restriction (Intermediate GMD=0.456kg) and C) Animals with food restriction (Low GMD = 0.154kg). After the rearing, the animals were fed to the finishing phase in feedlot, receiving equal diet among the treatments. At the beginning of the experiment 3 animals were slaughtered as reference, plus 2 animals per treatment in the transition between rearing and finishing, and the rest of the animals were slaughtered as they reached the pre-established weight of 400 kg of live weight. The live weight gain in the finishing phase did not differ between treatments, however, the feed restriction in the rearing contributed to a higher carcass yield at the termination, as well as an average daily carcass gain for animals with slight food restriction (53.5 and 69.0 %, respectively) when compared to animals with no growth restriction (51.8 and 60.0%, respectively). The feedlot time contributed to a greater deposition of subcutaneous fat, where steers that stayed 36 days longer in feedlot presented superiority of 25% of external fat in the carcass. It was concluded that there is no compensatory gain in the termination of super-precocious animals, being this strategy a technique to search for efficiency in carcass traits.